Food Irradiation Technology: An Overview of Practices and Status in the Globe and Bangladesh - Arefin, K S; Hassan, M; Suny, M S H; Sohag, M M H; Farukh, M A (Journal of Environmental Science and Natural Resources, 2025)
The agricultural food industry is giving priority to the development of technologies that guarantee product quality and safety as customers grow more conscious about food safety and health. Conventional thermal preservation techniques, such pasteurization and sterilization, frequently degrade food's nutritional value and texture. Alternative methods that preserve the stability and freshness of food items are becoming more popular in response. Among these technologies is food irradiation, which has been used for more than a century. Ionizing radiation is applied to packaged or bulk goods in the form of gamma rays from Cobalt-60 or Cesium-137, X-rays up to 5 MeV, or accelerated electrons up to 10 MeV. Without causing radioactivity in food or packaging, this technique improves microbiological safety, increases shelf life, and conforms to quarantine regulations. Conducted in shielded environments, food irradiation is recognized globally for its ability to ensure hygienic quality and reduce post-harvest losses. This paper provides an overview of food irradiation practices and their status in the Americas, the European Union, Asia, and Bangladesh, underscoring the technology's evolution, bene-fits, and widespread acceptance. Environ. Sci. & Natural Resources, 14(1&2): 65-71, 2025